PERANAN PERBANKAN DALAM UPAYA MEMBANTU TUGAS PUSAT PELAPORAN DAN ANALISIS TRANSAKSI KEUANGAN (PPATK) MENCEGAH TERJADINYA PENCUCIAN UANG - Trisna Dewi, Ni Made; Manika, Agus Surya (Kerta Dyatmika, 2023)
The Financial Transaction Reports and Analysis Center (PPATK) is an independent institution with a strategic role in preventing and combating money laundering crimes in Indonesia. This agency reports directly to the President and functions as a key partner to law enforcement authorities in uncovering money laundering cases. This research aims to examine the role of financial service providers, particularly banks, in assisting PPATK in the prevention of money laundering, as well as to identify the obstacles encountered by the banking sector in fulfilling this role. The research employs a normative legal method, focusing on the analysis of relevant statutory regulations. The findings indicate that banks, as financial service providers, play a vital role in supplying financial intelligence to PPATK derived from the analysis of submitted transaction reports. However, in practice, several obstacles are faced, including regulatory loopholes in the financial services sector, conflicts with other legislative frameworks, limitations in international cooperation both at the executive and judicial levels, and inadequate institutional capacity, such as the absence of an internal financial intelligence unit. In conclusion, the active involvement of banks is essential to support the performance of PPATK; nonetheless, regulatory reform and institutional capacity strengthening are necessary to address the existing challenges.